Modelos de Randall Sundrum e estabilização do raio da dimensão extra - Oliveira Júnior, Raimundo Ivan (2017)
In this dissertation we study The Randall Sundrum models type I and II and the stabilization of the radius of the extra dimension. Both the types were elaborated by Lisa Randall and Ramman Sundrum. The type I was developed to solve the gauge hierarchy problem (big discrepancy between the energy scale of the standard model(103GeV ) and the energy scale of the gravity (1019GeV ) . The type II explain, in details, the behavior of the gravity. We begin speaking of the extra dimensions models that preceded the Randall Sundrum model: Kaluza Klein, Arkani-Hammed- Dimopoulus-Dvali (ADD) and the Rubakov’s model ( The universe as a domain wall). Then, we make a review of the Lisa Randall and Ramman Sundrum papers. After that,we focus on the problem of the stabilization of the radius. This problem arises in the type I model. Lastly, we explain the solution that was created to it: The Goldberger Wise mechanism.